2018
DOI: 10.1111/are.13850
|View full text |Cite
|
Sign up to set email alerts
|

Modification of an agar well diffusion technique to isolate yeasts that inhibit Vibrio parahaemolyticus , the causative agent of acute hepatopancreatic necrosis disease

Abstract: Vibrio parahaemolyticus is the causative agent of acute hepatopancreatic necrosis disease. In this study, we isolated yeasts possessing inhibitory activity against V. parahaemolyticus. In general, the generation time of yeasts is longer than that of bacteria. Therefore, the techniques used to evaluate yeasts with activity against bacteria using the same incubation time may not be appropriate. In this work, an agar well diffusion technique was modified to resolve this problem. Various selected yeast colonies we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…As demonstrated in our previous study, the effect of indole on the virulence of V. cholerae has been investigated using G. mellonella larvae (Nuidate et al, 2016). Other studies have been evaluated the suitability of G. mellonella larvae as an alternative host of VP AHPND (Chalad et al, 2018) and V. campbellii (Kissalai et al, 2018), indicating the usefulness of this insect larvae as the infected model organism of shrimp pathogens. Our finding revealed that 1 mM indole reduced the virulence of VP AHPND in G. mellonella and shrimp larvae infection.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…As demonstrated in our previous study, the effect of indole on the virulence of V. cholerae has been investigated using G. mellonella larvae (Nuidate et al, 2016). Other studies have been evaluated the suitability of G. mellonella larvae as an alternative host of VP AHPND (Chalad et al, 2018) and V. campbellii (Kissalai et al, 2018), indicating the usefulness of this insect larvae as the infected model organism of shrimp pathogens. Our finding revealed that 1 mM indole reduced the virulence of VP AHPND in G. mellonella and shrimp larvae infection.…”
Section: Discussionmentioning
confidence: 97%
“…Other studies have been evaluated the suitability of G . mellonella larvae as an alternative host of VP AHPND (Chalad et al, 2018) and V . campbellii (Kissalai et al, 2018), indicating the usefulness of this insect larvae as the infected model organism of shrimp pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…The antifungal activity was determined by the agar well diffusion method [ 42 ]. Potato glucose Agar (PDA) medium was used for antifungal experiments.…”
Section: Methodsmentioning
confidence: 99%